Instalası FTTH ( Fıber To The Home ) Pada Konsumen PT Cıpta Informatıka Cemerlang - Gautama Wijaya; Avian Avian (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The utilization of information technology in everyday life has become a necessity for all of us. One example is the internet network or commonly called WiFi. This article describes the implementation of Job Training (KP) in a company engaged in the ISP ( Internet Service Provider ) in Batam City, named PT Cipta Informatika Cemerlang. The design and implementation of the WiFi installation is necessary because consumers at PT Cipta Informatika Cemerlang need an internet network for their needs. The author uses data collection methods in the form of observation and interviews. In the internet network installation stage, this research uses the PDDIE development method (Planning, Design, Development, Implementation, Evaluation). The results of this activity are implemented and used by consumers of PT Cipta Informatika Cemerlang